Two new species of South American Glaresidae (Coleoptera: Scarabaeoidea) - Paulsen, M.j. (Zootaxa, 2016)
Two new species of South American Glaresidae (Coleoptera: Scarabaeoidea) are described: Glaresis smithi Paulsen, new species from Argentina, and Glaresis mondacai Paulsen, new species from Chile and Peru. The species are compared to their closest congener, Glaresis fritzi Martínez et al., and a key is provided for the known South American species of the genus Glaresis Erichson.